Efficiency Analysis of Tanker Ship Fuel Usage by Applying Exhaust Gas Boyler and Turbo Generator Power Plant - Soemedyo Soemedyo; Muhammad Haddin; Agus Adhi Nugroho (Journal of Telematics and Informatics, 2018)
Efforts to save fuel consumption on tankers is absolutely necessary because in shipping it always faces waves and currents that inhibit the speed of the ship so that the shipping time is longer. If this happens, the fuel consumption of the ship will increase and waste will occur.This study aims to analyze fuel savings on tankers as oil supply vessels to meet domestic fuel needs. Savings are carried out by utilizing the heat energy of the exhaust gas of the propulsion main engine as a steam generator in the exhaust gas boiler (EGB). The steam production process takes place when the ship is in a sailing condition where the main engine has reached the maximum rotation. Exhaust gas boilers work with 16.5 bar pressure steam used as turbo generators to replace auxiliary engines to work as electricity generators as long as ships are on the cruise. In order to ensure the condition of the steam production system remains normal at work pressure so that the turbo generator working system remains stable for that exhaust gas boiler is equipped with automatic equipment both in the filling water supply system and ignition auxiliary boiler ignition system. Thus, as long as the ship is in shipping all the electricity needs are charged to the turbo generator, so practically with the application of this system resulting in savings in fuel consumption of MFO / MDO type vessels reaching 11.2% on each cruise. Keywords: Tanker ship, exhaust gas boiler, turbo generator, fuel efficiency